Clinico biochemical profile of birth asphyxia in neonates of western Odisha - Shah, Seema; Mishra, Pramila Kumari; Goel, Anil Kumar (Indian Journal of Child Health, 2014)
Background: Perinatal asphyxia contributes to almost 29% of neonatal deaths in developing countries as most of the deliveries occur in rural areas and are unattended. The outcome of most of the deliveries is not encouraging in spite of standard guidelines. Objectives: To study the different spectrum of clinical presentation of birth asphyxia and its biochemical derangements. Materials and Methods: This was a prospective, hospital-based study conducted from September 2005 to March 2008 comprising of 58 term neonates admitted to neonatal intensive care unit with definite history suggestive of perinatal hypoxic insult. Compilation of history, clinical features, and relevant investigations (random blood sugar, serum creatinine, blood urea and serum electrolytes) were done, and the results were analyzed by using Medcalc software version 12. Results: Vaginal delivery was more common across all the stages. Abnormal neonatal reflex was a common feature in all babies except hypoxic-ischemic encephalopathy (HIE) I. Convulsion, mostly multifocal seizures was present in allHIE II babies where as only 22.2% babies had seizure in HIE III. Congestive heart failure (55.17%) and Oliguria was present in HIE III (77.8%) and 22 cases (37.9%) developed acute kidney injury. Hypoglycemia was observed with increasing severity of asphyxia (HIE III 26.67 ± 2.78). Serum urea, creatinine and potassium increased significantly in HIE III whereas calcium and sodium were decreased. Conclusion: The combination of clinical and supportive laboratory parameters can be used for monitoring of patients to guide early intervention to decreases morbidity and mortality.